Birds of a Feather + Other Aerial Acrobats - Kulper, Perry (Architecture Image Studies, 2020)
Spatial storytelling, of all kinds, has structured cultural trajectories—grounding practices, customs and traditions, globally. This essay suggests the possibility of narrative spatial constructions as forms of world building—ways of setting out evidence, teasing out potential metaphorical crimes, as a form of creative participation, with a world. Through interfaces of spatial actors, actions, and situations, lush mini-cosmologies can be constructed—breaking boundaries, takings risks and putting the ‘form follows function’ paradigm, human-centric space, and temporal continuities, at risk. Trading on analogic thinking, surrealist tactics, and techniques of film making, the production of worlds in worlds, might enable retreat from other realities—a form of generative parallax. The potential of modes of visualization, coupled with the use of language, are important in generating alternative cultural, and non-human, imaginaries. Stimulating real and fictional skies, and distant horizons, this work fuels a creative imagination, challenging default assumptions, and reframing what is taken for granted.